The Effects of Different Dosage of Kefir with Different Durations on Growth Performances and Antioxidant System in the Blood and Liver Tissues of Coruh Trout (Salmo coruhensis) - Can, Erkan; Kurtoglu, Ilker Zeki; Benzer, Fulya; Erisir, Mine; Kocabas, Mehmet; Kizak, Volkan; Celik, Huseyin Tugrul (Central Fisheries Research Inst, 2012)
The objective of the present work is to examine the effects of different doses (0, 10, 20 and 40 g kg(-1) fish diet mass) of kefir on growth performance and oxidant-antioxidant status in the blood and liver tissues of Coruh trout, Salmo coruhensis, in different periods (2 and 3 months). In this study, survival was more than 88.3%, and irrespective of dietary kefir levels at the end of the study. There were no significant differences in SGR (Specific growth rate), FCR (Feed conservation rate), CF (Condition factor) among fish fed diets with 0, 10, 20 and 40 g kg(-1) kefir, however, these growth values were significantly different in terms of durations between 2-month and 3-month treatment (P<0.05). Our results indicated that TAS (Total Antioxidant Status) and TOS (Total Oxidant Status) in blood tissues reduced with kefir treatment at the end of third month (P<0.05). Malondialdehyde (MDA) levels in liver decreased in all groups compared with control group and a considerable extent decrease was observed in 40 g dose of kefir treatment at the end of third month. The data obtained from this experiment indicated that the same dose of kefir was more effective at the end of 3-month treatment than 2-month treatment (P<0.001). Although there was no statistical difference among groups, an increase in the glutathione peroxidase (GSH-Px) enzyme activity was observed in all groups compared to control groups. While catalase (CAT) activity decreased in all groups compared to control group at the end of second month (P<0.01), the decrease was insignificant level at the end of third month. In glutathione (GSH) levels, statistical differences were no observed in all groups compared to the control group with 2-month treatment while there were significant increases with 3-month treatment (P<0.001). It was concluded that kefir could play an antioxidant role and its effectiveness depended on dosage and time of application in Coruh trout, S. coruhensis.
Farklı doz ve sürelerde uygulanan kefirin çoruh alabalıklarının (Salmo coruhensis)kan ve karaciger dokularındaki oksidan ve antioksidan sistem ile büyüme performansı üzerine etkileri
Keywords: Salmo coruhensis; kefir; antioxidant; probiotic; growth